2021
DOI: 10.1371/journal.pone.0253714
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of co-composting organic biomass mixtures with inorganic amendments to obtain value-added bio-products

Abstract: Co-digestion of organic biomass mixed with inorganic amendments could have an impact on composting dynamics. Various studies highlighted fertilizers’ role as an additive to lesser the nitrogen loss, while some studies focused on the addition of fertilizers to enhance the efficiency. The changes in carbon, nitrogen components, and humic substances during the organic-inorganic co-compost process were seldom studied. Clarifying these changes might help improve the production process and compost nutrients contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“… 7 . Kitchen waste was then crushed in a grinder to reduce the size and increase surface area 8 . Tea waste (TW) which is residue that remains after cooking tea, was collected from local Café situated at Barkat market, Lahore.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 . Kitchen waste was then crushed in a grinder to reduce the size and increase surface area 8 . Tea waste (TW) which is residue that remains after cooking tea, was collected from local Café situated at Barkat market, Lahore.…”
Section: Methodsmentioning
confidence: 99%
“…During composting, the waste goes through a process of mineralization to convert binded elements into inorganic soluble forms. Consequently, when the compost is applied to the soils the nutrients are in bioavailable form and the plants can easily take them up 8 .…”
Section: Introductionmentioning
confidence: 99%
“…180 Chicken manure + sawdust increased compost bin temperature, pH, and oxygen, speeding organic−inorganic co-composting fermentation. 75 (3) Biological agents: The inoculation of biological agents can promote compost maturity, shorten the fermentation time, and help the nitrogen preservation and harmlessness of compost. 76 The microorganisms in the biological agent can convert a large amount of NH 4 + -N in the manure of livestock and poultry through nitrification into nitrate and then generate N 2 through denitrification, and NH 4 + -N can also be fixed into microbiological protein nitrogen, thereby reducing NH 4 + -N content, reducing the synthesis of NH 3 .…”
Section: Sws 25% Zeolitementioning
confidence: 99%
“…The data showed that adding inorganic fertilizers did not affect compost fermentation. This ingredient increased compost bin temperature, pH, and oxygen, speeding organic–inorganic co-composting fermentation …”
Section: Introductionmentioning
confidence: 99%
“…Different plant biomass resources has been used in the production of different types of manures in different countries, majorly compost or biochar [21][22][23][24][25][26]. The conversion of plant biomass to biochar or compost has gained attention as a potential solution for carbon sequestration and soil improvement, however, like any technology, there are concerns such as: High energy requirements, which can offset the potential carbon benefits of biochar production [27].…”
Section: Introductionmentioning
confidence: 99%